2023
DOI: 10.2147/ijn.s404494
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and ex vivo Skin Permeability Evaluation of Type I Collagen-Loaded Liposomes

Abstract: Purpose In the present study, we prepared collagen liposomes with the addition of polyol, which is expected to not only increase the solubility of collagen but also improve skin penetration. Methods Collagen liposomes were prepared by the film dispersion method, and their characteristics, integrity and biosafety were evaluated by Fourier transform infrared spectroscopy (FTIR), UV-VIS spectroscopy, polyacrylamide gel electrophoresis (SDS-PAGE), dynamic light scattering (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…29,30 Bioactive nanoparticles and nanocomposites have recently been demonstrated as potential applications to accelerate wound healing [31][32][33] using nanotechnology, including polymer-drug conjugates, polymer micelles, nanoparticles, composite particles, self-assembled lipid nanoparticles and liposomes for hydrophobic compounds delivery. [34][35][36] It is reported that Cur can be encapsulated in surfactant micelles to enhance its water solubility/dispersity. 37 Additionally, Cur nanoparticles with different sizes affect the therapeutic efficacy of curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Bioactive nanoparticles and nanocomposites have recently been demonstrated as potential applications to accelerate wound healing [31][32][33] using nanotechnology, including polymer-drug conjugates, polymer micelles, nanoparticles, composite particles, self-assembled lipid nanoparticles and liposomes for hydrophobic compounds delivery. [34][35][36] It is reported that Cur can be encapsulated in surfactant micelles to enhance its water solubility/dispersity. 37 Additionally, Cur nanoparticles with different sizes affect the therapeutic efficacy of curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38] Several nanocarrier formulations have been developed to enhance transdermal drug delivery, including liposomes, ethosomes, transfersomes, polymeric micelles, selfnanoemulsifying drug delivery system (SNEDDS), solid lipid nanoparticles (SLN), nanostructured lipid carriers (NLCs), and polymeric nanoparticles. [39][40][41][42][43][44] Despite the growing popularity of TDDS, there have been limited developments in formulations specifically for CBD. Nanocarriers formulation provides a promising platform for enhancing the delivery of CBD.…”
Section: Introductionmentioning
confidence: 99%
“… 27 For example, the topical application of solid lipid nanoparticles and nanostructured lipid carrier systems have been utilized with active compounds such as vitamin E (tocopherol), 28 retinoic acid, 29 and more. 30 , 31 Additionally, liposomes have been utilized to load anti-aging compounds such as type I collagen, 32 ferulic acid, 33 apigenin and doxycycline, 34 polyvinyl alcohol and gelatin, 35 and ligustrazine hydrochloride, 36 all of which have shown improved photoprotective effects with the utilization of the liposomal technology. Complexing lipids with polyphenols, termed lipophenols, have also been shown to be effective.…”
Section: Introductionmentioning
confidence: 99%